2014
DOI: 10.3109/02656736.2014.957738
|View full text |Cite
|
Sign up to set email alerts
|

A simulator for percutaneous hepatic microwave thermal ablation under ultrasound guidance

Abstract: The purpose of this study was to provide a simulation therapy environment for microwave thermal ablation (MWA) under the guidance of ultrasound, and to present an inexpensive and portable simulator built on real patient-based pre-operative computed tomography (CT) data. We established an experimental simulation system for teaching MWA and present the results of a preliminary evaluation of the simulator's realism and utility for training. The system comprises physical elements of an electromagnetic tracking dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…By calibrating the sensors, probe and MW antenna, the computer acquired and displayed information on real-time position and orientation of the US probe and the MW antenna. The accuracy and methods of calibration were verified in our previous studies [26,[28][29][30].…”
Section: Electromagnetic Tracking Devicementioning
confidence: 66%
See 1 more Smart Citation
“…By calibrating the sensors, probe and MW antenna, the computer acquired and displayed information on real-time position and orientation of the US probe and the MW antenna. The accuracy and methods of calibration were verified in our previous studies [26,[28][29][30].…”
Section: Electromagnetic Tracking Devicementioning
confidence: 66%
“…In previous studies [26][27][28][29][30], our research group developed and presented a 3D navigation software system that was applied to perform relevant experimental studies. These previous studies demonstrated that the navigation software could satisfy the clinical requirements of effectiveness, stability and security.…”
Section: Self-developed 3d Finsmentioning
confidence: 99%
“…60 An experimental simulation model for ultrasound-guided percutaneous microwave thermal ablation merges patient CT data with a phantom and electromagnetic tracking device, rendering real-time 3D procedural data and allowing for simulated procedural recording and playback. 61 AR may be applied in procedures real-time by fusing an overlay of imaging data onto a patient's body to facilitate anatomic targeting of needles, wires, catheters, and so on. 58 As a proof of concept, Solbiati et al 62 performed targeted needle insertion guided by AR on a phantom, porcine model, and cadaver.…”
Section: Virtual and Augmented Realitymentioning
confidence: 99%
“…Based on our previous studies [18][19][20][21], this study was designed as an experimental ex vivo study to verify the accuracy of needle targeting of self-developed 3D fusion navigation system for IG-MIT. The ex vivo study was performed by five medical students and five interventional radiologists.…”
Section: Experimental Designmentioning
confidence: 99%
“…In our previous studies [18][19][20][21], we developed a navigation software system and performed relevant experimental studies. These experimental studies included the I 125 particle implantation experiments of multineedle intervention and 3D visualization-based preoperative treatment planning Fig.…”
Section: Self-developed 3d Fusion Navigation Systemmentioning
confidence: 99%